The Revolution is Here How Artificial Intelligence (AI) is Transforming Education and Empowering the Next Generation of Learners - Chaurasia, P. K. (JOURNAL OF INDIAN EDUCATION, 2023)
The dynamic field of Artificial Intelligence (AI) within computer science is dedicated to the development of machines capable of emulating human-like intelligence, thereby executing tasks that traditionally require human cognitive abilities. While the concept of machines mirroring human cognition dates back to centuries, noteworthy instances, such as the automaton chess player, and the turing test emerged during the 18th and 20th centuries, respectively. AI employs algorithms and statistical models to analyse data, recognise patterns, and make decisions or predictions, effectively simulating human cognitive functions like learning, problem-solving, decision-making, perception, and language understanding. In contemporary society, AI has undergone profound transformations, influencing how we live, work, and communicate. Its significant strides have revolutionised various industries, rendering it an indispensable component of our daily lives and powering a myriad of day-to day applications. Of particular significance is AI’s transformative impact on education, reshaping it into a more personalised and accessible experience for students from diverse backgrounds. This article delves into the multifaceted applications of AI in education, offering an in-depth exploration of the ways in which this technology is redefining the educational landscape and enhancing everyday learning experiences. Moreover, this article incorporates recent research findings and advancements in the field of AI in education. It explores not only the current applications of AI but also the ongoing research efforts and breakthroughs that are contributing to the continuous evolution of AI-driven educational methodologies. The synthesis of practical applications and cutting edge research provides a comprehensive overview of the transformative role that AI plays in shaping the future of education, and empowering the next generation of learners.